Estimating near surface shear wave velocity using the SPAC method at a site exhibiting low to high impedance contrast. Issue 122 (July 2019) - Setiawan, Bambang; Jaksa, Mark; Griffith, Michael; Love, David
Abstract: In the general framework of seismic hazard analysis for quantifying site amplification, knowledge of the near surface shear wave velocity profile is crucial. The non-destructive and affordable ambient vibration array technique has been shown to be a superior method for estimating this shear wave velocity. The present study seeks to investigate the robustness of shear wave velocity profiles obtained using the ambient vibration array technique at sites exhibiting various (low to high) impedance contrasts by investigating a site in the central business district of Adelaide, South Australia. The city is founded on a regolith, which generally exhibits a range of impedance contrasts, and it is accepted that it is one of the Australian capital cities with the highest seismic risk. Eight ambient vibration array measurements were undertaken across the city. The acquired data were used to invert the shear wave velocity profiles, which are currently very limited, through the analysis of the dispersion characteristics of the surface waves by means of the spatial autocorrelation (SPAC) method, from which a further adjustment was carried out to suit the measured horizontal vertical spectral ratio (HVSR) curve ellipticity. Validation of the proposed shear wave velocity models was carried using previous studies and forward modeling techniques. The present study demonstrates that the SPAC method provides reliable results at regolith sites which are subject to various (low to high) impedance contrasts, provided the frequency band of the captured dispersion curve is wide enough to resolve the investigated depth. The primary innovations of this paper are to: (1) investigate the applicability of the microtremor SPAC method to obtain the near surface shear wave velocity of a low to high impedance contrast site; and (2) propose a new near surface shear wave velocity profile for Adelaide, South Australia. Highlights: This study seeks to investigate the robustness of shear wave velocity profiles obtained using the ambient vibration array technique at sites exhibiting various (low to high) impedance contrasts. Eight ambient vibration array measurements at regolith sites, which is subjected to impedance contrasts in the low to high range, were undertaken in the central business district of Adelaide, South Australia. The acquired data were used to estimate the shear wave velocity profiles through the analysis of the dispersion characteristics of the surface waves by means of the spatial autocorrelation (SPAC) method, from which a further adjustment was carried out to suit the measured horizontal vertical spectral ratio (HVSR) curve ellipticity. The estimates are validated using previous studies and forward modeling techniques. This work confirms that the SPAC method provides reliable results at regolith sites which are subject to various (low to high) impedance contrasts, provided the frequency band of the captured dispersion curve is wide enough to resolve the investigated depth.